Konsumsi Rokok Rumah Tangga Miskin di Indonesia dan Penyusunan Agenda Kebijakannya - Chriswardani Suryawati; Lucia Ratna Kartikawulan; Ki Haryadi (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: The number of smokers in Indonesia is ranked third in the world and the highest in ASEAN. The estimated number of deaths due to smoke from the 2004 Susenas data was 399,800 people equivalent to total economic loss of IDR 154.84 trillion (U.S. $ 17.2 billion), or 4.5 times as much as the tax equivalents in 2005 (IDR 32.6 trillion). Indonesia has not yet ratified the Framework Convention on Tobacco Control (FCTC) but has issued various regulations related to tobacco control and the dangers of smoking. Cigarette consumption by poor households is high enough. This affects not only the consumption patterns of the households but also the health of the family. Objective: To obtain a description of poor households’health cost burden, patterns and factors that affect cigarette consumption by poor households in Indonesia in 2007 and to set the agenda of public health protection policies of the dangers of smoking. Methods: The data used were the secondary data from the study of the Indonesia Family Life Survey (IFLS) conducted in 2007 covering 13 provinces, 13,995 households and 50,580 individual samples. Results and Discussion: A total of 35.71% of poor households had a habit of smoking, and the types of cigarettes were factory-made cigarettes and home-made cigarettes (81.81% and 29.19%, respectively). The average cigarettes consumed were 9.72 bars per day. The average age of initiating to smoke was 18.89 years and 93.20% of poor households were still smoking up to this survey. Compared to the total expenditure of poor households, the average expenditure of cigarettes a month was IDR 86,496.96 (13.13%), while health expenditure was only IDR 7,440.87 (1.13%). The low expenditure on health, among others, were due to the presence of Jamkesmas that covered 51.48%. Cigarette demand model with multiple regression analysis showed that the price of cigarettes, per capita expenditure, food expenditure, and the age of initial smoking affected cigarette consumption. Conclusions and suggestions: To make the policy of public protection on the dangers of smoking effective, the government should immediately formulate policy agendas: 1) increase cigarette tax as high as 50% of the price of cigarettes, 2) regulate restrictions on smoking areas in public places, 3) promote and campaign the dangers of smoking to health, especially for adolescents, including restrictionson cigarette advertising on various media 4) continue policy for cigarette tax revenue in all regions and increase allocation of funds for health, 5) facilitate the development of nicotine replacement treatments and make people easier to get the products, and 6) initiate to develop a Jamkesmas discourse that requires the poor households to maintain their health care such as not to smoke. It needs to further develop the understanding on public protection policy agenda against the dangers of smoking that consists of perceiving public problem, defining the problem and raising support for making this public issue become the the government agenda. Latar Belakang: Jumlah perokok di Indonesia menduduki peringkat tiga terbesar di dunia dan tertinggi di ASEAN. Estimasi jumlah kematian karena merokok dari data Susenas 2004 sebesar 399.800 orang setara dengan total economic loss sebesar Rp 154,84 trilyun (US$ 17.2 milyar) atau setara 4.5 kali lipat cukai tahun 2005 (Rp 32,6 triliun). Indonesia belum meratifikasi Framework Convention on Tobacco Control (FCTC) tetapi di Indonesia telah terbit berbagai peraturan terkait pengendalian tembakau dan bahaya merokok. Konsumsi rokok Rumah Tangga (RT) miskin cukup tinggi. Hal ini tidak hanya berpengaruh pada pola konsumsi RT tetapi juga kesehatan keluarga. Tujuannya adalah memperoleh deskripsi beban biaya kesehatan RT miskin, pola dan faktor yang berpengaruh pada konsumsi rokok RT miskin di Indonesia tahun 2007 dan menyusun agenda kebijakan perlindungan kesehatan masyarakat dari bahaya rokok. Metode: merupakan data sekunder dari penelitian Indonesia Family Life Survei (IFLS) yang dilaksanakan tahun 2007 mencakup 13 propinsi, 13.995 RT dan 50.580 sampel individu. Hasil dan diskusi : Sebanyak 35,71% RT miskin mempunyai kebiasan merokok, terbanyak sigaret (81,81%) dan rokok ramuan sendiri (29,19%). Rerata perhari 9,72 batang rokok, usia pertama kali merokok rata-rata 18,89 tahun dan 93,20% RT miskin masih merokok sampai survei dilakukan. Dibandingkan pengeluaran total RT miskin, rerata pengeluaran rokok sebulan Rp. 86.496,96 (13,13%) sedangkan pengeluaran kesehatan hanya Rp.7.440,87 (1,13%). Kecilnya pengeluaran kesehatan antara lain disebabkan adanya Jamkesmas yang mencakup 51,48%. Model demand rokok dengan analisis regresi berganda menunjukkan bahwa harga rokok, pengeluaran per kapita, pengeluaran pangan, umur awal merokok mempengaruhi konsumsi rokok. Kesimpulan dan saran: Untuk mengefektifkan kebijakan perlindungan masyarakat dari bahaya rokok maka pemerintah harus segera menyusun agenda kebijakan: 1). kenaikan cukai rokok karena cukai mencapai 50% dari harga jual rokok, 2). peraturan pembatasan area merokok di tempat-tempat umum, 3). promosi dan kampanye bahaya merokok terhadap kesehatan terutama untuk remaja termasuk pembatasan iklan rokok pada berbagai media 4). melanjutkan kebijakan bagi hasil cukai rokok pada semua daerah dan meningkatkan alokasi dananya untuk bidang kesehatan, 5) memfasilitasi pengembangan dan mem permudah mendapatkan produk nicotine replacement treatments 6). mulai mengembangkan wacana Jamkesmas yang mensyaratkan upaya RT miskin ikut menjaga kesehatannya antara lain tidak merokok. Perlu lebih mengembangkan pemahaman akan agenda kebijakan perlindungan masyarakat terhadap bahaya merokok yang terdiri dari persepsi masalah publik, pendefinisian masalah dan penggalangan dukungan untuk menjadikan isu publik menjadi agenda pemerintah.